Assessment of Corporate Social Responsibility performance and state promotion policies: a case study of The Baltic States - Lu, Jintao; Ren, Licheng; Zhang, Chong; Liang, Mengshang; Abrhám, Josef; Streimikis, Justas (Journal of Business Economics and Management, 2020)
The development of Corporate Social Responsibility (CSR) initiative is formed by several cultural, economic, social, political and institutional factors which have an impact on setting the priorities and advancement of CSR practices. The aim of this study is to assess CSR performance at the country level. In order to achieve this aim, the main drivers and barriers of CSR initiatives were identified and systematized based on literature review. The policies to address these barriers were analysed and discussed. The framework for the assessment of CSR performance was developed based on the analysis and assessment of the quality of political-regulatory, economic and social environment, implemented public policies to promote CSR and successes that were achieved by countries in implementing recommendations for public policy advancement. The indicators from Venture Capital and Private Equity Country Attractiveness Index, CSR policies areas reviews and EU recommendations for the improvement of public policies linked to the CSR were applied for assessing the CSR performance. The empirical analysis and the assessment of CSR performance in the Baltic States was performed based on the developed framework and policy recommendations that were developed for other countries, taking into account the priorities of “The Belt and Road” project that was initiated by the Chinese government and aiming at sustainable development and global risk mitigation.